Keratomycosis in a pet rabbit (Oryctolagus cuniculus) treated with topical 1% terbinafine ointment. (2nd October 2015) - Bourguet, Aurélie; Guyonnet, Alexandre; Donzel, Elise; Guillot, Jacques; Pignon, Charly; Chahory, Sabine
Abstract: This report describes the clinical presentation, diagnosis, and medical management of a 2‐year‐old spayed female dwarf rabbit ( Oryctolagus cuniculus ) suffering from an ulcerative keratitis and a stromal abscess with a rapid evolution. The diagnosis of fungal keratitis was based on fungal culture identifying the pathogen as Aspergillus fumigatus . Treatment by topical terbinafine was efficacious in resolving the keratomycosis within 8 weeks. To our knowledge, this is the first reported case of spontaneous keratomycosis in a rabbit and the first description of successful therapy by terbinafine.